E-cigarettes are not associated with post-acute COVID-19 syndrome among US adults - Shahryar Rajai Firouzabadi; Ida Mohammadi; Mohammadreza Alinejadfard; Arman Shafiee (Scientific Reports)
Abstract The COVID-19 pandemic has resulted in many survivors experiencing post-acute COVID-19 syndrome (PCS) with symptoms including fatigue, breathlessness, and cognitive complaints. E-cigarette use has already been associated with increased susceptibility to COVID-19 because of its effects on ACE2 receptor expression and inflammation, raising concern that it might worsen the long-term outcomes of COVID-19, including PCS. While traditional smoking is associated with a higher risk of PCS, the role of e-cigarettes remains unclear due to conflicting evidence. Using 2022 Behavioral Risk Factor Surveillance System (BRFSS) data, this study investigated the association between e-cigarette use and PCS among US adults who tested positive for COVID-19. The final sample included 107,249 adults after the exclusion of respondents with missing information. It analyzed e-cigarette use (never, former, current) and controlled for key covariates such as age, gender, BMI, smoking, and chronic diseases. The results showed that female gender, obesity, current smoking, and a history of depression, asthma, and chronic obstructive pulmonary disease (COPD) were significantly associated with higher odds of PCS. Nevertheless, e-cigarette use was not related significantly to increased odds for PCS (current e-cigarette use: aOR = 1.07, 95 CI: 0.96, 1.20; former e-cigarette use: aOR = 1.03, 95 CI: 0.96, 1.12). The mediation analysis showed no indirect effect of the use of e-cigarettes on PCS via COPD. In conclusion our findings did not reveal an independent or indirect association between PCS with e-cigarette use.